Non-linear material modeling of fiber-reinforced polymers based on coupled viscoelasticity–viscoplasticity with anisotropic continuous damage mechanics. (15th November 2015) - Vasiukov, D.; Panier, S.; Hachemi, A.
Abstract: A meso-scale material modeling of the fiber-reinforced polymer composites is presented. This model is based on coupled anisotropic viscoelasticity–viscoplasticity with anisotropic continuous damage mechanics. The constitutive equations are derived for three-dimensional statement and integrated implicitly by using return-mapping algorithm. Viscoelasticity model implies time dependent material properties. Viscoplasticity model is based on modified Hoffman criterion with combination of the Perzyna model. Anisotropic damage model is based on extended three-dimensional damage model. Developed material model is implemented in ABAQUS/Standard and is applied for modeling glass and carbon fiber laminate composite plates with various stacking sequences. Obtained results are in high agreement with already published experimental data.